2017
DOI: 10.1080/14756366.2017.1356295
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and carbonic anhydrase I, II, VII, and IX inhibition studies with a series of benzo[d]thiazole-5- and 6-sulfonamides

Abstract: A series of benzo[d]thiazole-5- and 6-sulfonamides has been synthesized and investigated for the inhibition of several human (h) carbonic anhydrase (CA, EC 4.2.1.1) isoforms, using ethoxzolamide (EZA) as lead molecule. 2-Amino-substituted, 2-acylamino- and halogenated (bromo-and iodo-derivatives at the heterocyclic ring) compounds led to several interesting inhibitors against the cytosolic hCA I, II and VII, as well as the transmembrane, tumor-associated hCA IX isoforms. Several subnanomolar/low nanomolar, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…The scaffold of the potent and isoform‐selective CA IX inhibitors of this type incorporates aromatic, heterocyclic, aliphatic, sugar, or combinations of such moieties, and is obviously highly important for the inhibitory activity, as it makes extensive interactions with the active site of the enzyme in the enzyme‐inhibitor complex (as shown by extensive X‐ray crystallographic studies) . Again, effective and isoform‐selective CA IX inhibitors were obtained from all these classes of derivatives mentioned here (examples will be disclosed shortly).…”
Section: Development Of Agents Targeting Carbonic Anhydrase IXmentioning
confidence: 95%
See 4 more Smart Citations
“…The scaffold of the potent and isoform‐selective CA IX inhibitors of this type incorporates aromatic, heterocyclic, aliphatic, sugar, or combinations of such moieties, and is obviously highly important for the inhibitory activity, as it makes extensive interactions with the active site of the enzyme in the enzyme‐inhibitor complex (as shown by extensive X‐ray crystallographic studies) . Again, effective and isoform‐selective CA IX inhibitors were obtained from all these classes of derivatives mentioned here (examples will be disclosed shortly).…”
Section: Development Of Agents Targeting Carbonic Anhydrase IXmentioning
confidence: 95%
“…As mentioned above, the main problem with the drug design of CA IX inhibitors was to obtain compounds which should selectively inhibit CA IX without a significant inhibitory effect against the physiologically dominant, highly abundant isoforms CA I and II (and also other off‐target isoforms) . This goal seemed to be difficult to achieve initially, but several classes of sulfonamides and their isosteres (sulfamates, sulfamides), most of which were obtained using the tail approach, allowed to obtain compounds with these features . Only the most relevant studies will be mentioned here, as this class of CAIs is the most investigated one and a high number of drug design studies (>400) have been reported since 2003 .…”
Section: Development Of Agents Targeting Carbonic Anhydrase IXmentioning
confidence: 99%
See 3 more Smart Citations